Practical approach to diagnosis of bland-looking spindle cell lesions of the breast - Magro, G.; Salvatorelli, L.; Puzzo, L.; Piombino, E.; Bartoloni, G.; Broggi, G.; Vecchio, G.M. (Pathologica - Journal of the Italian Society of Anatomic Pathology and Diagnostic Cytopathology, 2019)
The diagnosis of bland-looking spindle cell lesions of the breast is often challenging because there is a close morphological and immunohistochemical overlap among the different entities. The present review will discuss reactive spindle cell nodule/exuberant scar, nodular fasciitis, inflammatory pseudotumor, myofibroblastoma (classic type), lipomatous myofibroblastoma, palisaded myofibroblastoma, benign fibroblastic spindle cell tumor, spindle cell lipoma, fibroma, leiomyoma, solitary fibrous tumor, myxoma, schwannoma/neurofibroma, desmoid-type fibromatosis, dermatofibrosarcoma protuberans, low-grade fibromatosis-like spindle cell carcinoma, inflammatory myofibroblastic tumor and low-grade myofibroblastic sarcoma arising in the breast parenchyma. The pathologist should be aware of each single lesion to achieve a correct diagnosis to ensure patient a correct prognostic information and therapy. Accordingly representative illustrations and morphological/ immunohistochemical diagnostic clues will be provided.